2006
DOI: 10.1080/02688690601048104
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler ultrasonography as an early outcome forecaster following severe brain injury

Abstract: Knowledge of post-traumatic cerebral haemodynamic disturbances might be beneficial for predicting the management outcome when measuring the basal cerebral arteries blood flow velocity by ultrasonic transcranial Doppler device immediately after severe head injury. Thirty patients who sustained severe brain injury underwent an early blood velocity measuring by transcranial Doppler ultrasonography during a 1-year period of study. The standard technique of measuring the mean blood flow velocity in the middle cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…TCD flow velocity measurements follow the same trend as pre-clinical studies discussed above, most indicating an increase in PI with pathology [130-141], and good correlation with clinical condition [139,142]. Using a technique similar to that of Eide described above, Splavski et al showed good correlation between the degree of elevated PI and the duration of time (in hours per day) for which the mean ICP was elevated (ICP > 25 mmHg) [138].…”
Section: The Intracranial Pulse Wave - Clinical Studiesmentioning
confidence: 69%
“…TCD flow velocity measurements follow the same trend as pre-clinical studies discussed above, most indicating an increase in PI with pathology [130-141], and good correlation with clinical condition [139,142]. Using a technique similar to that of Eide described above, Splavski et al showed good correlation between the degree of elevated PI and the duration of time (in hours per day) for which the mean ICP was elevated (ICP > 25 mmHg) [138].…”
Section: The Intracranial Pulse Wave - Clinical Studiesmentioning
confidence: 69%
“…In the observational study of Splavski et al also, have concluded that measuring the MCA blood velocity after TBI is a worthy tool to estimate ICP, as well as to evaluate early post-traumatic cerebral haemodynamics (24).…”
Section: Gura M Et Al: Correlation Of Pulsatility Index With Intracrmentioning
confidence: 99%
“…Further research is needed to establish the gold standard and validate findings in children [ 20 ]. By calculating linear regression equations, Splavski, 2006, demonstrated that each additional unit of PI value will be reduced by 2.613 units in the Glasgow Outcome Score (GOS) 6 months later [ 21 ]. PI and GOS showed similar trends at 3 and 12 months after TBI in our cohort study.…”
Section: Discussionmentioning
confidence: 99%